Doppler vertical sounding of the ionosphere at the Akademik Vernadsky station - A. Zalizovski; O. Koloskov; A. Kashcheyev; S. Kashcheyev; Y. Yampolski; O. Charkina (Ukrainian Antarctic Journal, 2020)
The paper aims at providing the technical information about Doppler vertical sounding of the ionosphere that started at the Ukrainian Antarctic Akademik Vernadsky station since 2017; developing the technique for processing and visualization of data of vertical sounding of the ionosphere in the form of height-time diagrams of median values of ionospheric parameters; demonstrating the capabilities of this technique using the results obtained during the first year of observations, namely the background variations of ionospheric parameters as well as examples of observations of travelling ionospheric disturbances (TID). The methods used in the paper are the following: the vertical sounding of the ionosphere using the IPS-42 ionosonde operating at Akademik Vernadsky station since 1982; Doppler vertical sounding of the ionosphere by the portable ionosonde developed and manufactured in collaboration between the Abdus Salam International Centre for Theoretical Physics (ICTP) and Institute of Radio Astronomy of the National Academy of Sciences of Ukraine (IRA NASU); calculating the height-time diagrams of ionospheric parameters obtained using the data of both ionosondes; and original technique for estimating the median height-time diagrams as background monthly averaged characteristics of the ionosphere. Seasonal and diurnal variations of plasma frequencies, vertical plasma velocities, as well as the signal-to-noise ratio and the probability of the registration of signals are shown using the median height-time diagrams of the corresponding parameters for the first year of synchronous observations by the two ionosondes. The features and potential areas of application of median ionospheric height-time diagrams are discussed. They can be used to calculate automatically variations of maximum usable frequency for a radio link of the specified length. Examples of TID registrations in variations of virtual heights of reflection and Doppler frequency shifts (DFS) of the signals are presented. It is shown that the comparison of TID manifestations in variations of virtual heights and DFS can be used to select a more appropriate model of TID among the models of perfectly reflecting moving surface or three-dimensional plasma density waves traveling through a real ionospheric layer. It could be concluded that simultaneous operation of two ionosondes at the Akademik Vernadsky station has allowed to significantly expand the amount and quality of objective information about the ionospheric behavior over the Antarctic Peninsula.